PENGELOLAAN LAHAN PEKARANGAN/KEBUN DENGAN SENGON SOLOMON HASIL KULTUR IN VITRO PADA KELOMPOK USAHA PEMBIBITAN SENGON DI KABUPATEN MALANG - Kusmawati, Wiwik; Zaini, Moh.; Ernata, Yusvidha (JPM Pambudi, 2018)
Sengon nursery business groups, especially in Poncokusumo Subdistrict and Wajak Subdistrict, Malang Regency still rely on sengon seeds that grow wild in nature with low growth rates. Though sengon seeds are a commodity of high economic value. This can be seen from the small number of breeders who manage the sengon seeds well. Even though the availability of plant seeds is a factor that plays a major role in the success of the sengon plant forest development program. Quality seeds with the support of aquaculture technology can provide high quality seeds so they can produce quality trees and wood products. The stages of implementing PKM activities are as follows: (a) Survey and planning, (b) Counseling and training "Optimization of Yard / Garden Land Management with Sengon Solomon Results of In Vitro Culture in Sengon Nursery Groups in Malang Regency", and (c) Cultivation Solomon's sengon seeds from in vitro culture. The results achieved through this community service program are resolving some of the partners 'problems, namely sengon breeders still rely on sengon seeds that grow wild in nature, lack of sengon seedlings, lack of public understanding of solomon sengon cultivation technology, limited breeders' ability to seed sengon, and low superior sengon seeds produced, which have an impact on the amount of sengon seedlings produced. The activities carried out have succeeded in supporting the service program, namely counseling and training on "Optimizing the Management of Yard / Garden Land with Sengon Solomon Results of In Vitro Culture in Sengon Nursing Business Groups in Malang Regency", and cultivating the seeds of sengon solomon from in vitro culture.